Persepsi Pengunjung Terhadap Keberadaan Wana Wisata Puncak Damar dalam Pelestarian Hutan - Intan Okta Mulyana; Endah Djuwendah (Paspalum: Jurnal Ilmiah Pertanian, 2018)
This research to identify the characteristics of visitors and analyze the perception of visitors to management of Wana Wisata Damar Peak in forest conservation. Visitor perseption in review of service, infrastructure, environment (physical, social, and culture), and forest conservation. The research location in Pakualam Village, Darmaraja Subdistrict, Sumedang Regency, West Java Province from late june to erly july 2017. Research design is a quantitative design using survey method. Data collegtiorn using interviews, observation, and literature study. The selection of sample using simple random sampling, with the number of respondents as many as 100 people. Research result indicated that most ofvisitors came from Sumedang, male gender, aged between 20 – 29 years old, with high school education as a student and have income less than Rp 1.000.000, the purpose of visiting in general for a vacation because this place is attractive  and cheap entry fees, most visitors budgeted for the cost of recreation per mont less than Rp 200.000. Almost half of the visitors came with friends using their own vehicles, doing a one-time visit and interested to visid again. Visitor perception to management of Damar Peak in the forest conservation is still not good because the manager and the community is still lacking in the effort of forest conservation.